THE PRINCIPLE OF RENEWAL OF POETIC SYMBOLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article talks about the principles of renewal of poetic symbols in the new Uzbek poetry. The innovations in symbols and images in the work of Fitrat and Cholpon, the leading representatives of the new Uzbek poetry, were revealed during the analysis.